2021
DOI: 10.3390/brainsci11030351
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Visual and Oculomotor Alterations in a Clinical Population of Children with and without Neurodevelopmental Disorders

Abstract: A prospective, non-randomized comparative study was conducted to compare the distribution of oculomotor and visual alterations in children with neurodevelopmental disorders and healthy children without such disorders. Sixty-nine children (aged 6–13 years) were enrolled and divided into three groups: a control group (CG) of 23 healthy children; a group of 18 healthy children with oculomotor abnormalities (OAG); and a group of 28 children with a neurodevelopmental disorder (NDDG), with 15 cases of dyslexia, 7 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Significant differences between CG and NDDG were found in all the categories evaluated with the NSUCO test, with worse outcomes in the group of children with neurodevelopmental disorders, as in previous studies [ 10 , 12 ]. Likewise, significant differences were found in some parameters provided by the eye tracking system, including the number of hypometric saccades and the percentage of hypometric saccades with respect to the number of completed saccades.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Significant differences between CG and NDDG were found in all the categories evaluated with the NSUCO test, with worse outcomes in the group of children with neurodevelopmental disorders, as in previous studies [ 10 , 12 ]. Likewise, significant differences were found in some parameters provided by the eye tracking system, including the number of hypometric saccades and the percentage of hypometric saccades with respect to the number of completed saccades.…”
Section: Discussionsupporting
confidence: 80%
“…However, the diagnostic criteria defined for the diagnosis of these conditions are not consistent, with no normative data available to be used for diagnostic purposes [ 18 ]. Different authors [ 10 , 11 , 12 , 13 , 14 , 19 , 20 ] have demonstrated the presence of oculomotor anomalies in children with neurodevelopmental disorders, but using different types of tests, parameters and cutoff criteria, being quite difficult a generalization of the diagnostic criteria and how to use this information to analyze the impact of oculomotor anomalies in daily activities, such as reading or playing sports. Furthermore, the scientific evidence of the correlation between subjective and objective tests to analyze oculomotor performance is scarce and showing poor correlation between both types of examination [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations